Comparison of the fuel properties and the combustion behavior of PET bottle caps with lignite. (October 2017) - Unal, Nurdan Irem; Mertdinc, Siddika; Haykiri-Acma, Hanzade; Yaman, Serdar
Abstract: This study focuses on evaluation of used PET bottle caps as energy resource. Fuel properties of PET bottle caps were determined considering proximate analysis and HHV. In addition, combustion properties were investigated based on DSC profile and the functionalities were determined by FTIR technique. The fuel properties of PET were compared with those of a Turkish lignite, concluding that the HHV of PET is 3.5 times higher than that of lignite, what shows that using PET in energetic purpose may be promising approach. There are some important differences on the burning characteristics and functional groups of lignite and PET samples.